Chemical Composition, Total Phenolic Content, and Antioxidant Activity of the Essential Oils Extracted from the Needle of Ten Pinus Taxa - Zhihong Liu; Weixin Fan; Qing Xie (Journal of Chemistry)
This study investigated the chemical compositions of essential oils (EOs) from ten taxa belonging to the Pinus genus. The studied taxa that grow wildly in China, and the EOs were extracted by steam distillation; the chemical compositions were isolated and characterized by GC-MS. Eighty-one components, representing over 92.10% of the EOs, were identified. The main constituents of EOs were α-pinene (6.44%–53.00%), β-caryophyllene (2.43%–24.64%), β-pinene (0.00%–22.32%), δ-cadinene (2.56%–17.56%), germacrene D (0.74%–11.38%), and camphene (0.78%–10.48%). Furthermore, we determined the total phenolic content (TPC) of the EOs, with the values from 26.50 to 60.01 mg eq GAE/mL EO. DPPH free radical scavenging activity (DPPH), ferric reducing antioxidant power (FRAP), and ABTS radical cation scavenging activity (ABTS) were used to evaluate the antioxidant capacity of the EOs, and the obtained values were ranged from 499.15 to 1,272.75 mmol eq Trolox/mL EO, 1,255.67 to 3,857.93 mmol eq Trolox/mL EO, and 370.81 to 1,677.19 mmol eq Trolox/mL EO, respectively. The results showed that all of the EOs studied had strong antioxidant activity, and these pine plants could be used as natural antioxidants in functional food and pharmaceutical industries.